Toughening Polylactide Stereocomplex by Injection Molding with Thermoplastic Starch and Chain Extender - Yottha Srithep; Dutchanee Pholharn; Patnarin Worajittiphon; Keartisak Sriprateep; Onpreeya Veang-in; John Morris (Polymers, 2023)
The high cost, low heat resistance, and brittleness of poly(L-lactide) (PLLA) is a significant drawback that inhibits its diffusion into many industrial applications. These weaknesses were solved by forming a polylactide stereocomplex (ST) and blending it with thermoplastic starch (TPS). We blended poly (L-lactide)(PLLA), up to 30% thermoplastic starch, and a chain extender (2%) in an internal mixer, which was then hand-mixed with poly (D-lactide)(PDLA) and injection molded to form specimens, in order to study mechanical, thermal, and crystallization behavior. Differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (XRD) demonstrated that the stereocomplex structures were still formed despite the added TPS and showed melting points ~55 °C higher than neat PLLA. Furthermore, stereocomplex crystallinity decreased with the increased TPS content. Dynamic mechanical analysis revealed that ST improved PLLA heat resistance, and tensile testing suggested that the TPS improved the elongation-at-break of ST. Moreover, the chain extender reduced the degradation of ST/TPS blends and generally improved ST/TPS composites' mechanical properties.
Keywords: biodegradable polymer synthesis and properties; Additive Manufacturing and 3D Printing Technologies; Polymer Foaming and Composites